Le Liban-Sud entre deux générations de réformistes - Sabrina Mervin (Revue des Mondes Musulmans et de la Méditerranée)
The monthly journal al-'Irfân, published in Saida, was the Shi'ite counterpart of al-Manâr. Since its creation just after the Young Turk Revolution in 1908, the journal published the reformist ideas of clergy and educated men, who were mostly Shi'ite and who originated from the Jabal 'Amil (which, after the creation of Greater Lebanon in 1920, became Southern Lebanon). A true forum for discussion, the journal was the place where all issues were debated from political and religious questions to problems in society. Its founder, Ahmad 'Arif al-Zayn (1884-1960), opened the pages of the journal to all those who wished to express themselves. The overall tone of the journal was reform and Arab nationalism as expressed by educated persons. 'Âmili clergy also published articles in al-'Irfân, in which some of them exposed their reformist ideas. Among them was Muhsin al-Amin (1867-1952), one of the most important 'Âmilî mujtahid and a reformer of the 'Ashûrâ rites.